EXPLORING MEANINGFUL CHILD PARTICIPATION IN GOVERNANCE: INSIGHTS FROM BARANGAY LOCAL GOVERNMENT UNITS IN SOUTHERN PHILIPPINES - Argie Khim Ormilla; Christine Tenorio (Yayasan Wayan Marwan Pulungan, 2024)
This study examines how the selected barangay local government units (BLGUs) in the Southern Philippines are implementing meaningful child participation in governance. It focuses on three key aspects: informing children of their rights, actively hearing their perspectives, and involving them in decision-making. The study found a diverse group of respondents, with a majority from Gen Z and Millennials. Many are college graduates and actively involved in organizations, showcasing their potential as future leaders. A significant effort is put into ensuring children are well-informed about their rights under the UN Convention on the Rights of the Child (UNCRC). This highlights a commitment to both inclusivity and upholding children's rights. The research also found a positive perception towards